Att styra Generation Z : En explorativ studie i syfte att förbättra styrningen av nästa generation - Kylmänen, Jonathan; Blomdahl, Anton (Luleå tekniska universitet, Institutionen för ekonomi, teknik och samhälle, 2018)
Management happens in all organizations. An important part of the management area is motivation. Motivating individuals within the organization leads to more efficient work and higher target compliance. In order to be able to manage, it’s important to know what the individuals are motivated by. Previous research has shown that different generations are motivated by different things. Today's technological society has led to fact that the latest generation, Generation Z, has had a different upbringing which may distinguish them from previous generations. This may affect how they look at work and what motivates them at work. The purpose of this paper is to identify the motivational factors that organizations should take into account in order to best manage Generation Z. In order to achieve the purpose, two studies were conducted. Interviews were conducted with two people belonging to Generation Z, the interviews were the basis for the essay's main survey, the questionnaire. The questionnaire was conducted at Luleå Gymnasium, where all the students belonged to Generation Z. In total, 113 respondents answered the questionnaire, but three of the answers were incomplete, which mean that 110 answers were the basis for the analysis. To analyse the questionnaire, hypothesis testing has been used. The result shows that meaningful tasks, clear goals and feedback are factors that Generation Z are motivated by. The result also shows that organizations operate best through situational management, as motivation factors differ between individuals within the generation. The essay contributes knowledge in how organizations should best manage the latest generation that now enters the market. Styrning sker i alla organisationer. En viktig del inom styrningsområdet är motivation. Att motivera individerna som är verksamma inom organisationen leder till effektivare arbete och högre målöverrensstämmelse. För att lyckas bäst med styrning är det därför viktigt att veta vad individerna motiveras av. Tidigare forskning har visat att olika ...